Decision Support System Internet Disruption Using ORESTE and Geolocation PT Cloud Solution - Zakaria Mubarok, Adhi; Supriyono, Supriyono; Latifah, Noor (Universitas Negeri Padang, 2025)
PT Cloud Solution is a cloud-based internet service provider located in Kudus, Central Java, and serves the Kudus, Pati, and Jepara areas. The main problem in PT Cloud Solution's operations is the process of reporting and handling internet service disruptions which are still done manually, without an integrated system and without utilizing customer location data. This causes delays in technician responses, inaccuracies in technician distribution, and the absence of a prioritization system based on the level of urgency of the disruption. This study aims to develop a web-based Decision Support System (DSS) that integrates the Organization, Rangement Et Synthèse De Données Relationnelles (ORESTE) method and geolocation technology to support the decision-making process in determining the priority of damage handling. The ORESTE method is used because it is able to process ordinal data and perform an objective ranking of alternatives without a complex weighting process. Geolocation technology is implemented to map the position of customers and technicians in real-time, so that the system is able to recommend handling based on location proximity and priority scale. The system was developed using the Waterfall model with stages of needs analysis, design using Use Case diagrams, implementation with PHP language and MySQL database, and tested using the Black Box method. Test results show that the system is capable of generating accurate and efficient handling priorities. This system is expected to improve the speed and accuracy of technician distribution, and customer satisfaction